Seres Vivos. Nivel I. Basado en el curso de estudios de Ciencia de Montgomery County Public Schools - Senger, Graciela; Montgomery County Public Schools, Rockville, MD. Office of Instruction and Program Development ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
This curriculum unit, developed by the Montgomery County Public Schools, Maryland, was designed for use in the elementary level foreign language immersion program. It is geared toward the first grade science classroom. The unit includes instructional and performance objectives, necessary vocabulary lists, optional language structure sections, activities, evaluation suggestions, and worksheets. The unit considers topics such as seeds, plants, growth, life, movement, fruits and vegetables, reproduction, food, and plant- and animal-based products. With the exception of instructional objectives, all materials are written in Spanish. (SR)
Sponsoring Agency: Department of Education, Washington, DC.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavioral Objectives; Class Activities; FLES; Foreign Countries; Grade 1.; Immersion Programs; Primary Education; Science Instruction; Second Language Learning; Spanish; Units of Study; Vocabulary; Guides, Classroom -- Teacher